Atmospheric mercury emissions from China's primary nonferrous metal (Zn, Pb and Cu) smelting during 1949–2010. (February 2015) - Ye, Xuejie; Hu, Dan; Wang, Huanhuan; Chen, Long; Xie, Han; Zhang, Wei; Deng, Chunyan; Wang, Xuejun
Abstract: Primary nonferrous metal smelting is one of the most significant anthropogenic mercury emission sources. A spatially resolved mercury emission inventory over a long time span is essential for assessment of mercury source attribution and mercury transport modeling. In this study, based on updated technology-based emission factors, the atmospheric mercury emissions originating from primary zinc, lead and copper smelting in China were calculated. The inventory indicated that the total mercury emission from nonferrous metal smelting in China was 14.65 Mg in 2010, lower than the estimations in previous studies. The contributions of point and non-point sources were 23.3% and 76.7%, respectively. In 2010, the mercury emission from primary zinc, lead and copper smelting was 7.49, 6.05 and 1.10 Mg, respectively, and the Hg 2+, Hg 0 and Hg P emissions were 8.10, 6.16 and 0.75 Mg, respectively. Spatially, the province with the largest emission was Sichuan, followed by Henan, Gansu, Shaanxi, Hunan and Yunnan provinces. The historical emissions were estimated based on dynamic emission factors that take the temporal technology changes into consideration. During 1949–2010, the cumulative mercury emission from China's nonferrous metal smelting was 323.0 Mg, of which the emission from lead smelting accounted for 44.6%, followed by zinc smelting (32.8%) and copper smelting (22.6%). From 1949 to 2010, the contribution of mercury emission from zinc smelting increased from 1.4% to 53.7%, while that from lead smelting showed a decreasing trend. For copper smelting, its contribution reached the maximum (40.1%) in 1987. Highlights: High-resolution mercury emission from nonferrous metal smelting is calculated. Mercury speciation information is involved in the inventory. A dynamic historical inventory with mercury species is developed.